The phase transformation and electrochemical properties of TiNi alloys with Cu substitution: Experiments and first-principle calculations. (12th January 2017) - Zhang, Z.; Elkedim, O.; Ma, Y.Z.; Balcerzak, M.; Jurczyk, M.
Abstract: Cu substituted TiNi alloys have been investigated as hydrogen storage material for Ni-MH batteries by experiments and first principle calculations. The amount of Cu (x in TiNi1−x Cux ) is varied from 0.1 to 0.3. All of samples were prepared by mechanical alloying using a planetary high-energy ball mill and subsequent heat treatment at 750 °C for 0.5 h. The structural transformation was characterized by X-ray diffraction method (XRD) and scanning electron microscopy (SEM). It indicated that mechanical alloyed TiNi1−x Cux alloys possessed broad diffraction peaks related to BCC structure. After heat treatment, studied TiNiCu materials consisted of Ti(Ni, Cu) B 2 phase as main phase. The cell parameter of B 2 phase increased linearly with increasing Cu content. The influence of Cu substitution for Ni in TiNi cubic phases was investigated by first principle calculation. It is found that TiNi0.7 Cu0.3 possessed the most negative enthalpy of formation. The stability of TiNi1−x Cux phase increased with Cu content. The width of valence bands was enlarged by substituting Cu atom. The discharge capacities of annealed samples were tested by electrochemical measurements at galvanostatic conditions. The results showed that the substitution of Cu for Ni seemed to deteriorate the activation properties of TiNi based alloys. Among all of studied materials, unmodified TiNi showed the highest discharge capacity which is equal to 154 mAh/g. Accompanying the substitution of Cu for Ni, the discharge capacity and cycling abilities of Cu substituted TiNi alloys declined and increased, respectively. All of the substituted samples exhibited at least 97% retaining rate after 20 cycles. Highlights: A series of TiNi1−x Cux (x = 0, 0.1, 0.2, 0.3) alloys was prepared by mechanical alloying and heat treatment. The phase transformations and electrochemical properties of studied materials have been characterized and analyzed. The lattice parameters and enthalpy of formation of Ti(Ni, Cu) cubic phase have been determined by first-principles calculations. The influence of Cu substitution on the structure and electrochemical behavior of TiNi-based alloys have been discussed. All of Cu substituted TiNi alloys exhibited at least 97% retaining rate after 20 cycles.